Pendidikan Seni Sebagai Media Konstruksi Indentitas Generasi Z: Tinjauan Teori Konstruktivisme Sosial Vygotsky - ronald candra (Journal of Innovative and Creativity, 2025)
This study originates from the phenomenon of Generation Z students born between 2001 and 2010 who, due to rapid technological advancement, have developed a strong dependency on the internet and social media in their daily activities. Their identity construction is often centered on virtual existence, expressed through images, videos, symbols, and avatars shared on digital platforms. In this context, education should play a crucial role in guiding Generation Z to distinguish between virtual spaces and real social environments. Art education serves not only to develop aesthetic appreciation and technical skills but also functions as a reflective, expressive, and symbolic medium in the process of self-exploration and identity formation. This research employs a qualitative descriptive method using Vygotsky’s Social Constructivism theory as its analytical framework. The main research question is: How does Art Education (in terms of School, Identity, and Digital Media) serve as a medium for constructing Generation Z’s identity through the perspective of Vygotsky’s Social Constructivism? Data were collected through literature review of relevant books and peer-reviewed journal articles. The findings indicate that art education, particularly in the context of Generation Z, plays a significant role as a medium for identity construction that is not only aesthetic but also reflective and socially engaged. Through the lens of Vygotsky’s theory, students’ identities are shaped through social interaction and the use of cultural tools, including digital media. In art education, digital media function as a form of social mediation that fosters visual literacy, identity reflection, and value negotiation within participatory spaces. Keywords: Art Education, Self-Identity, Generation Z, Social Construction